2022
DOI: 10.3390/agronomy12112906
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rhizospheric Fungus on Biological Control of Root Rot (Fusarium equiseti) Disease of Saposhnikovia divaricata

Abstract: Saposhnikovia divaricata is a high-demand medicinal plant containing various bioactive metabolites (e.g., chromone). However, root rot disease leads to a dramatic reduction in the yield and quality of S. divaricata. The use of rhizospheric microorganisms is one of the best strategies for biological control. In this study, a total of 104 fungi isolated from the rhizospheric soil of S. divaricata plants were examined for their different antifungal properties. Subsequently, strain MR-57 was selected as a potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
(41 reference statements)
0
0
0
Order By: Relevance
“…Antibiosis of selected bacterial strains. The five isolates selected based on their growth inhibition percentage calculated during the dual culture assay were further studied for their in vitro antibiosis activity [39]. Liquid LB media (25 mL for each repetition) were inoculated with 1 mL of fresh bacterial culture (OD at 595 nm = 1) in 50 mL conical centrifuge tubes.…”
Section: In Vitro Biocontrol Activitymentioning
confidence: 99%
“…Antibiosis of selected bacterial strains. The five isolates selected based on their growth inhibition percentage calculated during the dual culture assay were further studied for their in vitro antibiosis activity [39]. Liquid LB media (25 mL for each repetition) were inoculated with 1 mL of fresh bacterial culture (OD at 595 nm = 1) in 50 mL conical centrifuge tubes.…”
Section: In Vitro Biocontrol Activitymentioning
confidence: 99%
“…Previous studies revealed that chromones, coumarins, and volatile oils are the main active components of S. divaricata [ 1 , 6 , 7 ], and are responsible for its analgesic, anti-cancer, anti-inflammatory, anti-pyretic, anti-convulsant, and anti-coagulant effects [ 1 , 8–11 ]. Previous studies of S. divaricata have mainly focused on its pharmacological effects [ 9 , 12–14 ], biocontrol potential of rhizospheric fungus [ 15 , 16 ], physiological and ecological characteristics [ 17 ], transcriptomics [ 18 ], and antioxidant activity [ 19 ]. To date, little information is available about the genetic diversity and evolution of S. divaricata .…”
Section: Introductionmentioning
confidence: 99%